Pemilihan Moda Transportasi Semarang – Jakarta Dengan Metode AHP Menggunakan Expert Choice - Saputro, Daniel Tunggono (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
One of the supports for improving a country's economy is the availability of various modes of transportation that can be accessed or used by all communities to support activities such as work, trade, school, medical treatment, etc. Jakarta is the capital of Indonesia, is the center of business, trade, government, etc., so of course many people head to the city of Jakarta to carry out various activities. Likewise, people from the city of Semarang travel to the city of Jakarta to carry out various activities. Research was carried out on the choice of transportation modes from the city of Semarang to the city of Jakarta using the Analytical Hierarchy Process (AHP) method with data processing using Expert Choice software and the resulting choice of the mode of transportation was private cars as the main alternative with a weight of 31.9% and the next alternative was airplanes ( 30.9%), train (23.9) and bus (13.3%). The main selection criteria is travel time with a weight of 28.5%, and the next criteria are cost (25.7%), safety (20.2%), reliability (15.3%) and comfort (10.4%). And the inconsistency rate of this research is 3%.